Sour cherry anthracnose and possibilities of the control with special regard to resident Glomerella population in sour cherry plantations of East Hungary - Oros, Gyula; Vajna, László; Balázs, Klára; Fekete, Zoltán; Naár, Zoltán; Eszéki, Eszter (Acta Agraria Debreceniensis, 2010)
Anthracnose is considered one of the most destructive diseases for sour cherry production due to the rapid development of the disease on fruits. Glomerella cingulata (Stoneman) Spauld. & H. Schrenk (anam.: Colletotrichum gloeosporioides (Penz.) Penz. & Sacc. in Penz.) has been the fungal pathogen responsible for anthracnose in last decades. Yield losses greater than 90% may occur under epidemic conditions. C. acutatum (J.H. Simmonds, 1968) strains were isolated of sourcherry plantations in East Hungary and this pathogen, new for Hungarian microbiont became recently dominant. Contrarily to the former species it is certainly transmitted with ants during fruit ripening. About third of strains proved to be cutinase producers that enable them to actively penetrate via cuticule, and these strains infect directly berries of blackberry, grape and tomato as well as plum and apple. Most of cutinase negative strains could also infect these fruits after mechanic injury. All strains of both species produce amylase, cellulase, lecithinase, lipase, polyfenoloxydase and protease in vitro, although the activity of these enzymes highly varied in the medium. The only C. acutatum strains produced noticeable amount of chitinase. Strains, tolerant to recently applied fungicides to control the anthracnose, could be isolated of sour cherry plantations that might be the cause of ineffectiveness of control measures in 2010. The mycofungicide containing mixture of three Trichoderma species in oil carrier could efficiently depress the development of anthracnose in ripening sour cherry.